DESIGN OF ATK RETAIL INFORMATION SYSTEM AT LIPPO WHOLESALE STORE USING DRIVEN DEVELOPMENT MODEL METHOD - Agya Putri Nabila; Vera Wijaya; Harry Pratama Figna (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
At this time to face various challenges, especially in the era of information digitalization, of course, one must be smarter in choosing the strategy that will be used for the process of running a company, currently many companies are using business-to-business and business-to-consumer models. In other words, many companies have used the business transaction model for vendor companies and other business organizations such as manufacturers and wholesalers. Lippo Wholesale Store is a trading business which is engaged in selling ATK (Office Stationery). In the sales system procedures still use a manual system, where data processing is still using SpreadSheet, with the increasing number of merchandise, problems arise, namely the difficulty of getting inventory information quickly, precisely and accurately. The cause of the emergence of these problems is the processing of transaction data requires several stages and frequent recording errors in invoices, forms and reports are made, in the customer data section there is often an error in recording the number of orders, this causes losses that are owned by lippo wholesale stores. Utilization of retail information systems combined with model driven development methods canoptimize performance and time efficiency, so as to increase sales at Lippo Wholesale Stores.